قراءة في مفهوم "فصاحة الكلمة" في ضوء علم الأصوات الحديث - كتانة, حسين; زاهيد, عبد الحميد (Sciences humaines; Vol. 25 (2012): SCIENCES HUMAINES, 2014)
لقد تنبه البلاغيون القدماء إلى أهمية المستوى الصوتي في الدرس البلاغي والنقدي، وذلك منذ المؤلفات البلاغية الأولى، كالبيان والتبيين للجاحظ والصناعتين للعسكري. ونحن في هذا المقال سنسعى إلى تبيان مستوى وعي هؤلاء البلاغيين بدور المكون الصوتي في معالجة الظاهرة الأدبية، وذلك بتقديم قراءة في مفهوم "فصاحة الكلمة" من منظور علم الأصوات الحديث. وقد خلصنا إلى وجود مدارس صوتية واتجاهات متكاملة في تراثنا النقدي والبلاغي هدفها مقاربة فصاحة الكلمة، في النص الأدبي، وذلك بالنظر إلى تلاؤم عنصري السلسلة الصوتية: الصوامت والصوائت   Classical Retoricians have realized the importunce of the phonological of the phonological study within the rhetorical and critical Erame work since the first rhetorical publications like "Al-Bayan wa Al tabyan " for AL-Jaheth and "AL- sna tayn" for AL- Askry. In this paper, the researchers will explaine the level of awarnce of these ritori cians towards the role of the phonological study in literary studies through the concept of " standard word" from the point of view of the modern phonological studies. Results show that there are comprehensive phonological school and trendsin our Oritical and rhetorical heritage and that their aim is the study of the "standard word " in the literary text taking in consideration the suitability of the phonological chain (Vowels and Consonants).